Wybrane problemy dydaktyczne w nauczaniu przedmiotu systemy informatyczne w rachunkowości - Emerling, Izabela; Wójcik-Jurkiewicz, Magdalena (Selected Issues in Teaching Computerized Accounting Systems, 2005)
Contemporary employment market requires that graduates should be able to use their knowledge and skills flexibly, according to changing requirements of employers. Modern teaching purposes have to emphasize: independence and responsibility, thinking and self-perfection, activity and creativity. In teaching of computerized accounting systems it is possible to use most of practical or problem-sensitive methods, for example: coincidence method, situation method, didactic games, brain-storming and a lot of others. Popularization and usage of these methods in practice may increase the quality of education.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 35-42